2013
DOI: 10.1093/mnras/stt1886
|View full text |Cite
|
Sign up to set email alerts
|

The soft component and the iron line as signatures of the disc inner radius in Galactic black hole binaries

Abstract: The inner radius of the accretion disc around a black hole in the low/hard state can be measured in one of two ways. Firstly, via the extent of broadening of the iron emission line, and secondly, from the luminosity and temperature of the weak soft component seen in this state, assuming it is the disc. We use both of these methods on all the low/hard state spectra taken in timing mode of XMM-Newton 's EPIC-pn. We find that the two methods are not consistent with each other, and the difference is not always in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
82
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(96 citation statements)
references
References 47 publications
11
82
3
Order By: Relevance
“…Previous analyses of the same (or part of the) data sets analysed in this paper (Wilkinson & Uttley 2009;Kolehmainen et al 2014) revealed the presence of a significant contribution from the accretion disc-thermal emission in the soft band. Thus we used the XMM-Newton data to measure the disc-thermal emission-to-total flux ratio in the soft band and verify whether the drop of fractional rms is related to spectral variations in this band.…”
Section: Is the Disc Variable Or Constant During The Hard State?mentioning
confidence: 54%
See 2 more Smart Citations
“…Previous analyses of the same (or part of the) data sets analysed in this paper (Wilkinson & Uttley 2009;Kolehmainen et al 2014) revealed the presence of a significant contribution from the accretion disc-thermal emission in the soft band. Thus we used the XMM-Newton data to measure the disc-thermal emission-to-total flux ratio in the soft band and verify whether the drop of fractional rms is related to spectral variations in this band.…”
Section: Is the Disc Variable Or Constant During The Hard State?mentioning
confidence: 54%
“…tbabs * [diskbb+nthcomp], with the Comptonization high energy cut-off fixed at 100 keV and the seed photon temperature tied to the disc temperature), and excluding the range of energies 4 − 7 keV, dominated by the Fe Kα line. We also excluded the energies around the edges of the response matrix, since residuals at these energies might be an artifact of uncorrected XRL effects and/or charge transfer inefficiency (Kolehmainen et al 2014). The contribution from the disc emission strongly depends on the cold absorption column density parameter, N H .…”
Section: Is the Disc Variable Or Constant During The Hard State?mentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, one should avoid using detectors which are severely affected by this effect (Done & Díaz Trigo 2010). Kolehmainen, Done & Díaz Trigo (2014) (hereafter KDD14) calculated the inner radius both from the modelling of the disc and that of the reflected component using the data taken by the XMM-Newton EPIC-pn detector in timing mode. Though their study indicates highly truncated disc, the radii calculated by the two methods do not agree with each other.…”
Section: Introductionmentioning
confidence: 99%
“…This spectral shape is generally described as unsaturated Compton scattering of the soft X-ray photons from the accretion disk by thermal electrons in hot inner flow or corona. Previous studies suggested that the standard disk is truncated in the low/hard state and eventually extends inward according to the increase of X-ray luminosity (Tomsick et al 2009;Shidatsu et al 2011b;Yamada et al 2013;Kolehmainen et al 2014). However, in what luminosity the standard disk reaches the ISCO is still controversial.…”
Section: Introductionmentioning
confidence: 99%